Optimal movement decisions in complex landscapes - Line S. Cordes; Charles M. Bishop; Luca Börger; Jacob Nabe-Nielsen; Stephanie M. Harris (Trends in Ecology & Evolution, 2025)

The importance of developing modeling frameworks to inform conservation decisions: a response to Lonergan - Jason Matthiopoulos; Sophie Smout; Marjolaine Caillat; Line Cordes; Beth Mackey; Paul Thompson (Oecologia, 2014)

Mark‐recapture modeling accounting for state uncertainty provides concurrent estimates of survival and fecundity in a protected harbor seal population - Line S. Cordes; Paul M. Thompson (Marine Mammal Science, 2014)
Harbor seal breeding behavior and habitats constrain opportunities for individual‐based studies, and no current estimates of both survival and fecundity exist for any of the populations studied worldwide. As a result, the drivers underlying the variable trends in abundance exhibited by harbor seal populations around the world remain uncertain. We developed an individual‐based study of harbor seals in northeast Scotland, whereby data were collected during daily photo‐identification surveys throughout the pupping seasons between 2006 and 2011. However, a consequence of observing seals remotely meant that information on sex, maturity‐stage, or breeding status was not always available. To provide unbiased estimates of survival rates we conditioned initial release of individuals on the first time sex was known to estimate sex‐specific survival rates, while a robust design multistate model accounting for uncertainty in breeding status was used to estimate reproductive rate of multiparous and ≥3‐yr‐old females. Survival rates were estimated at 0.95 (95% CI = 0.91–0.97) for females and 0.92 (0.83–0.96) for males, while reproductive rate was estimated at 0.89 (0.75–0.95) for multiparous and 0.69 (0.64–0.74) for ≥3‐yr‐old females. Stage‐based population modeling indicated that this population should be recovering, even under the current shooting quotas implemented by the recent management plan.

State-space modelling reveals proximate causes of harbour seal population declines - Jason Matthiopoulos; Line Cordes; Beth Mackey; David Thompson; Callan Duck; Sophie Smout; Marjolaine Caillat; Paul Thompson (Oecologia, 2014)